A new approach for modelling insolation from the space perspective - Prakhova, Sofya (Curtin University, 2014)
In this thesis we present a new approach for modelling insolation from the space perspective. The incoming radiation was modelled as a flux passing through a cross-section (latitudinal belt), and the changes of light throughout the year were represented by an ellipse with changing parameters. The modelling approach used allows the incorporation of the impact of space activity (such as solar flares, galactic radiation and so on) on the Earth’s climate.